2006
DOI: 10.1186/1740-3391-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters of the suprachiasmatic nuclei

Abstract: There has been extensive research in the recent past looking into the molecular basis and mechanisms of the biological clock, situated in the suprachiasmatic nuclei (SCN) of the anterior hypothalamus. Neurotransmitters are a very important component of SCN function. Thorough knowledge of neurotransmitters is not only essential for the understanding of the clock but also for the successful manipulation of the clock with experimental chemicals and therapeutical drugs. This article reviews the current knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 272 publications
2
76
0
8
Order By: Relevance
“…Thus, the lateral geniculate nucleus, through the geniculohypothalamic tract, provides a secondary, indirect photic input to the suprachiasmatic nucleus as well as an alternate input which has an important role in entrainment of circadian rhythms (6). This is further supported by other studies (7)(8)(9)(10)(11)that have reported that the lateral geniculate nucleus is an important component of the circadian timing system and is responsible for the integration of photic and non-photic information to modify suprachiasmatic nucleus activity.Since the histology and functioning of the suprachiasmatic nucleus is altered during trypanosomosis (12), this study investigated the effect of T.b.…”
Section: Introductionsupporting
confidence: 75%
“…Thus, the lateral geniculate nucleus, through the geniculohypothalamic tract, provides a secondary, indirect photic input to the suprachiasmatic nucleus as well as an alternate input which has an important role in entrainment of circadian rhythms (6). This is further supported by other studies (7)(8)(9)(10)(11)that have reported that the lateral geniculate nucleus is an important component of the circadian timing system and is responsible for the integration of photic and non-photic information to modify suprachiasmatic nucleus activity.Since the histology and functioning of the suprachiasmatic nucleus is altered during trypanosomosis (12), this study investigated the effect of T.b.…”
Section: Introductionsupporting
confidence: 75%
“…This research could be of particular importance at the present time, as providing an alternative mechanism for electro-environmental modulation of melatonin levels specifically, and of circadian and seasonal rhythms in general. Hofman (2004) notes that the endocrine activity of the pineal gland is influenced by neural input from the suprachiasmatic nucleus (SCN) Environmentalist (2008) 28:307-314 311 which itself receives both retinal input and serotonergic input from the midbrain (Reghunandanan and Reghunandanan 2006). Changes in serotonin activity could thus impact both directly and indirectly on melatonin and other rhythms.…”
Section: Conclusion and Remediationmentioning
confidence: 99%
“…Nitric oxide (NO) is mainly produced by endothelial Nitric Oxide Synthase (eNOS) and its bioavailability follow circadian dependent pattern (Reghunandanan and Reghunandanan, 2006;Antosova et al, 2009). NO is a major player in the regulation of the cardiovascular system and reduced NO bioavailability has been linked to cardiovascular disorders (Andrade et al, 2013).…”
Section: Introductionmentioning
confidence: 99%